Fluctuating neurological symptoms in demyelinating disease mimicking an acute ischaemic stroke. (3rd April 2012) - Delgado, Montserrat G; Santamarta, Elena; Sáiz, Antonio; Larrosa, Davinia; García, Raquel; Oliva, Pedro
Abstract : Fluctuating neurological symptoms in an older patient most often point towards a cerebral ischaemic pathology. The authors present a 66-year-old male patient suffering from a fluctuating right hemiparesis, with an initial diagnosis of ischaemic stroke. The brain and cervical MRI showed demyelinating lesions with abnormal cerebrospinal fluid (CSF) and visual evoked potentials and the patient was successfully treated with intravenous corticosteroids. Demyelinating disease in older patients could be more frequent than expected. It should be considered even in older patients with fluctuating neurological symptoms. MRI and CSF analysis are critical to provide an accurate diagnosis.